2015
DOI: 10.1158/0008-5472.can-15-0356
|View full text |Cite
|
Sign up to set email alerts
|

Depleting MET-Expressing Tumor Cells by ADCC Provides a Therapeutic Advantage over Inhibiting HGF/MET Signaling

Abstract: Hepatocyte growth factor (HGF) and its receptor MET represent validated targets for cancer therapy. However, HGF/MET inhibitors being explored as cancer therapeutics exhibit cytostatic activity rather than cytotoxic activity, which would be more desired. In this study, we engineered an antagonistic anti-MET antibody that, in addition to blocking HGF/MET signaling, also kills MET-overexpressing cancer cells by antibody-dependent cellular cytotoxicity (ADCC). As a control reagent, we engineered the same antibody… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…42 ARGX-111 inhibits ligand-dependent cMET activation and shows cytotoxic activity in both cMET-expressing human cancer cells and patient-derived chronic lymphocytic leukemia and acute myeloid leukemia cells. In an orthotopic mouse model, ARGX-111 decreased the number of circulating tumor cells and suppressed metastasis.…”
Section: Anti-cmet Antibodiesmentioning
confidence: 99%
“…42 ARGX-111 inhibits ligand-dependent cMET activation and shows cytotoxic activity in both cMET-expressing human cancer cells and patient-derived chronic lymphocytic leukemia and acute myeloid leukemia cells. In an orthotopic mouse model, ARGX-111 decreased the number of circulating tumor cells and suppressed metastasis.…”
Section: Anti-cmet Antibodiesmentioning
confidence: 99%
“…Drug resistance remains a vexing problem in the treatment of cancer patients. The aberrant activation of HGF and its receptor MET has been strongly implicated in the malignant transformation and progression of several tumours 8,24 and is frequently implicated in resistance to targeted therapies 25,26 . Feng et al found that significantly greater frequencies of high HGF and MET receptor expression were observed in ALK-positive NSCLC patients 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evaluations of these molecules using the aforementioned criteria was needed to identify the best pair of anti-EGFR and anti-c-Met Abs to be put into the JNJ-61186372 BsAb design. A recent report of an antagonistic anti-Met antibody with Fc engineering has been described to have enhanced ADCC activity 50 . This antibody outperformed an ADCC-dead version of the antibody that could still inhibit c-Met signaling in multiple mouse models 50 …”
Section: Discussionmentioning
confidence: 99%